Digital Media as Medium to Create Learners’ Understanding, Knowledge Construction and Behavioral on Social Media Engagement in Teaching and Learning - Mohamed, Rozita Naina; Rusli, Mohd. Saifullah (Advances in Social Sciences Research Journal, 2024)
In the contemporary era, digital media, facilitated by electronic devices, has transformed the way individuals connect and communicate globally. This study investigates the synergy between digital media platforms used and face-to-face teaching methods in the classroom as tools to foster learners' understanding, knowledge construction, and behavior in the realm of social media engagement. By examining the application of these techniques, the study aims to transcend traditional boundaries in higher education, exploring their impact on student interaction and resource transfer. Drawing on a literature review, focus groups, and an in-depth survey involving the Business and Management Faculty at UiTM, this empirical study utilizes collaborative learning and interactivity among students and lecturers. 96 self-administered questionnaires were collected from a sample of 150 respondents, employing a university intercept approach. The results reveal significant positive effects on social media engagement concerning learners' understanding, knowledge construction, and behavior. Additionally, socio-demographic variables such as age, education, and ethnicity play influential roles. The findings underscore the transformative potential of digital media in collaborative learning, fostering student engagement, creativity, and a dynamic, learning-oriented environment. This study contributes valuable insights into the evolving landscape of digital education, emphasizing the limitless possibilities for information acquisition in a digitally connected world.